Alcohol‐Focused Behavioral Couple Therapy. Issue 3 (2nd July 2016) - McCrady, Barbara S.; Wilson, Adam D.; Muñoz, Rosa E.; Fink, Brandi C.; Fokas, Kathryn; Borders, Adrienne
Abstract : Alcohol Behavioral Couple Therapy (ABCT) has emerged over the last 30 years as a highly efficacious treatment for those with alcohol use disorders. This review highlights the historical and conceptual underpinnings of ABCT, as well as the specific treatment elements and structure. Proposed active ingredients, moderators, and mediators of treatment outcome are discussed. Efficacy is evaluated for reductions in identified patient drinking, improved relationship functioning, and reductions in intimate partner violence. Adaptations of ABCT for substances other than alcohol are described. Other adaptations, including brief interventions, interventions addressing PTSD and TBI along with alcohol use, and interventions deliverable via technology platforms are described. Additional cost‐benefit and cost‐effectiveness findings supporting the economic value of ABCT are noted. Future directions for research in this area include possible adaptations for female identified patients, nontraditional couples, LGBT partners and dyads involving nonintimate partner relationships. The development of more flexible models and enhanced dissemination strategies may improve clinical uptake and utility as well as increasing the feasibility of this treatment for integrated healthcare settings.